Standardisation and categorization of indigenous microorganisms (IMOs) for inoculated deep litter piggery in India - YADAV, SEEMA; BHARTI, P K; GAUR, G K; DEVI, BHANITA; ABHISHEK, ABHISHEK; SAHOO, N R; CHHABRA, RAJESH; SOMAGOND, ARUN; ANTIL, MOHIT (The Indian Journal of Animal Sciences, 2020)
The present experiment was conducted on standardisation and categorization of Indigenous Microorganisms (IMOs) in India for its future application as inoculum in inoculated deep litter housing of pigs. The cultivation of IMOs was accomplished in four steps, which involved use of half cooked rice, sugar sources, rice bran and soil at 1st, 2nd, 3rd and 4th steps, respectively. The cultivated IMOs at the end of each step from 1st to 4th were named accordingly as IMO-1, IMO-2, IMO-3 and IMO-4. The cultivation of IMOs was done in three groups based on the major sources of energy at 2nd step as control (brown sugar), treatment 1 (Jaggery) and treatment 2 (Molasses). The IMO-1 was obtained after 7 days which was confirmed based on the appearance of white coloured fungal mycelium in all the groups. The IMO-4 was considered as the final product of cultivation process which was confirmed by the presence of fungal mycelium interwoven in the soil. IMO-4 stage was further categorised in different microbial groups based on laboratory examination and only two categories of microbes were witnessed namely bacteria and fungi, none of yeast were found in those inoculums. Out of four types of bacterial colonies, IMB-3 confirmed the presence of Paenibacillus amylolyticus and IMB-4 as Enterococcus casseliflavus. The standardisation of IMOs as inoculum for deep litter housing was performed first time in India.